Alcohol Consumption and Gastrointestinal Cancer Risk: A Scoping Review - Agung Subakti Nuzulullail; Amalia Khasanah Ima Dudini; Aulia Diah Rahayu; Avantika Puspa Imelda Wensi; Dita Aditia Mamonto; Dhiana Ayu Novitasari; Dwina Oktavia Deli; Mukaromah Mukaromah; Riyati Riyati; Wa Ode Umi Kalsum; Wiwin Lismidiati (Universitas Muhammadiyah Semarang, 2025)
Cancer is one of the leading causes of death worldwide, including gastrointestinal cancer, which continues to increase in prevalence. One contributing risk factor is long-term alcohol consumption. This study aims to determine the relationship between alcohol consumption and the incidence of gastrointestinal cancer. The study design used a scoping review through four databases, namely ScienceDirect, PubMed, SpringerLink, and Medline. Articles were selected based on inclusion and exclusion criteria, with the screening process following the PRISMA 2020 guidelines. The selected articles were then synthesized using the Guidance for Conducting Systematic Scoping Review (2020) guidelines. A total of seven articles met the criteria. Various types of gastrointestinal cancer related to alcohol consumption were found, including colorectal, esophageal, stomach, and liver cancer, and even breast cancer. Most studies examined current and past patterns of alcohol consumption. Overall, the findings of this study prove that alcohol consumption, whether in the past, present, or cumulative, is associated with an increased incidence of gastrointestinal cancer, especially colorectal cancer.